Government support mechanisms and their role in financing small and emerging enterprises in Algeria - Abed, BECHIKR (The journal of contemporary issues in business and government, 2023)
Interest in small enterprises is increasing in the economies of countries, due to the role they have become and the strategic position they occupy in light of regional and international transformations, and the problem of financing small enterprises, along with the problem of growth, is one of the most important difficulties they face, so the most important aspect of financing is this aspect in which it is noted that the verses and financing formulas available to small and medium enterprises are inadequate, which calls for the need to work on introducing new formulas for financing, as well as Benefiting from the experiences of developed countries in this field, in addition to taking care and working to upgrade the alternatives available locally and that suffer from deficiencies and incompatibility with the distinctive financing needs of this type of institutions, and highlighting alternatives through which future prospects can be foreseen to advance the field of financing small and medium enterprises in the world in general and Algeria in particular.